Oral contraceptives and MS disease activity in a contemporary real-world cohort - Bove, Riley; Rankin, Kelsey; Chua, Alicia S; Saraceno, Taylor; Sattarnezhad, Neda; Greeke, Emily; Stuart, Fiona; LaRussa, Allison; Glanz, Bonnie I; Chitnis, Tanuja (Multiple sclerosis, 2018)
There is uncertainty regarding the effect of oral hormonal contraceptives (OC) on multiple sclerosis (MS) course. To evaluate the hypothesis that OC use is associated with decreased risk of relapses in an observational study of women of childbearing age with new-onset MS starting a first-line injectable disease-modifying therapy (DMT). From our CLIMB longitudinal observational study, we identified 162 women with MS or CIS with known OC use who initiated injectable DMT within two years of symptom onset, and categorized OC use at DMT onset as past, ever or never. Our primary analysis was comparison of annualized relapse rate from baseline DMT start across the three OC use categories using a negative binomial regression model. In this cohort of 162 women, 81 were treated with interferon therapy and 81 with glatiramer acetate. Mean ages for current-, past-, and never-OC users were 31.4 ( n = 46), 40.3 ( n = 66), and 37.9 ( n = 50) years, respectively ( p < 0.05); mean disease duration (1.0 years) and median baseline EDSS (1.0) did not differ between groups. Prior OC users had significantly lower relapse rates than never-users ( p = 0.031); the lower annualized relapse rate in current-users relative to never-users was not significant ( p = 0.91). Annualized relapse rate was not significantly different across the OC groups ( p = 0.057, three-group comparison). These observations provide reassurance for women newly diagnosed that OC use, past or current, does not appear to be associated with greater risk of relapses.